The Effectiveness of Blended Learning in Improving Students - Anum Dahlia; Bertha Musty; Atep Aulia Rahman (English Journal Literacy Utama, 2020)
The advancement of technology and the age of the industrial revolution 4.0 today have changed the way people learn and acquire information. The availability of internet access and the large use of computers and smartphones in a campus environment can be directed to carry out the learning reform and to obtain the course learning outcomes. Therefore, blended learning as one method of choice was adopted to be implemented to achieve the learning outcomes. The study aimed to investigate the effectiveness of blended learning to improve students' English speaking ability. The participants of the study were 48 fourth-semester students, and the study was conducted for one semester in the English Business Conversation class. The research methods used were quantitative and qualitative. The use of quantitative in this research was to measure students